Analysis of radio frequency interference mitigation using two reference antennas and closure relations in interferometric arrays - Nguyen, B.; Sutinjo, Adrian; Wayth, Randall (2018)
© 2018 IEEE. Radio-frequency interference (RFI) is a critical problem in radio astronomy observations. A powerful RFI mitigation technique introduced by Briggs in 2000, uses closure relations and an independent reference signal to estimate and effectively remove RFI term from the power spectra of dish-based telescopes. However, the proposed technique assumes reference antennas receive zero or negligible astronomical signal, which causes biased error in the outcome of cancellation, especially for low-frequency interferometric arrays with wide field of view (FoV). This paper revisits the proposed technique for RFI removal of interferometric arrays using two reference antennas with significant sky signal. The relationship between the residual error of the cancellation and the pattern of the reference antenna is investigated, providing a general guideline on design specifications of the reference antennas. This analysis potentially leads to further application in any wide FoV telescopes to alleviate the contamination of terrestrial FM and Digital TV RFI broadcast signals in radio astronomy observations.